2018
DOI: 10.1007/s10618-018-0573-y
|View full text |Cite
|
Sign up to set email alerts
|

Constrained distance based clustering for time-series: a comparative and experimental study

Abstract: et al.. Constrained distance based clustering for time-series: a comparative and experimental study. Data This is the author's version of an article published in Data Mining and Knowledge Discovery. The final authenticated version is available online at: https://doi.org/10.1007/s10618-018-0573-y.Abstract Constrained clustering is becoming an increasingly popular approach in data mining. It offers a balance between the complexity of producing a formal definition of thematic classesrequired by supervised methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 94 publications
0
15
0
Order By: Relevance
“…The relevance of pairwise constraints in semi-supervised clustering has been thoroughly investigated in the literature-e.g. see(Lampert et al 2018) for a recent study in the realm of time-series.…”
mentioning
confidence: 99%
“…The relevance of pairwise constraints in semi-supervised clustering has been thoroughly investigated in the literature-e.g. see(Lampert et al 2018) for a recent study in the realm of time-series.…”
mentioning
confidence: 99%
“…Also, they showed that K-medoids is better in terms of execution time, non sensitive to outliers, reduces noise and minimizes the sum of dissimilarities of data objects. Lampert et al [21] also showed the limits of the K-means algorithm under some constraints.…”
Section: Related Workmentioning
confidence: 99%
“…Constrained clustering algorithms broadly fall into six categories: k-Means, Metric Learning, Spectral Graph Theory, Ensemble, Collaborative, and Declarative. An in-depth review of all appraoches is presented in [5]. This work focusses on k-Means approaches, including one example from collaborative clustering, as they are ubiquitous in remote sensing.…”
Section: Constrained Clusteringmentioning
confidence: 99%